Environmental evolution of western Tierra del Fuego (-54°S) since ice-free conditions and its zonal/hemispheric implications - Moreno, Patricio I.; Lambert, Fabrice; Hernandez, Loreto; Villa Martinez, Rodrigo Patricio (My University, 2023)
By virtue of its position adjacent to the Drake Passage, Tierra del Fuego in South America allows examining the vegetation and environmental history of the southernmost continental landmass outside Antarctica, and the evolution of the Southern Westerly Winds-Southern Ocean (SWW-SO) coupled system since the Last Glacial Maximum (LGM). For that purpose, we studied sediment cores from Lago Charquito, a small closed-basin lake in central-west Tierra del Fuego with a continuous lacustrine record since-17.3 ka. Ice-free conditions at the site imply a-70 km retreat of the Bahia Inutil glacier lobe from its LGM position during a-800-year interval, a trend that continued until its disappearance-100 km upstream from L. Charquito,-800 years later. Our palynological data show an open landscape dominated by cold-tolerant shrubs and herbs between-17.3-12.9 ka, with increases in precipitation of SWW origin at-16.3 ka,-14.7 ka, between-8.7-7.6 ka, and after-6.8 ka. Warming at-12.9 ka initiated an abrupt afforestation trend that stalled during the early Holocene (-12-8.7 ka) owing to a precipitation decline and wildfires, and later resumed in response to invigorated SWW. We hypothesize that sparse Nothofagus tree populations inhabited the periphery of the Patagonian Ice Sheet (PIS) during the LGM and migrated toward the Andes contemporaneous with glacier recession as temperature rose during the Last Glacial Termination (T1). We posit that besides establishing topographic and climatic barriers for land biota, the PIS enabled the connectivity of cold-tolerant hygrophilous plant populations along a humid fringe adjacent to its land-based perimeter, despite the presumably dry conditions downwind from the eastern PIS margin. Our results suggest that southward shifts or expansion of the SWW toward or beyond Tierra del Fuego enhanced upwelling and ventilation of deep waters in the SO, northward shifts or weakening had the opposite effect. We observe that the time evolution of atmospheric CO2 concentrations, high-latitude air and sea-surface temperatures, and sea level during T1 fall short in explaining the timing and abruptness of the Bahia Inutil glacier lobe collapse, and quite possibly multiple other glacier lobes from the PIS.
Keywords: Last Glacial Maximum; Tierra; Westerlies; Chronology; Stadial; Nothofagus; Biota; Paleoclimatology